Recurrent Pneumonia With Tuberculosis and Candida Co-infection Diagnosed by Metagenomic Next-Generation Sequencing: A Case Report and Literature Review - Ma, Ning; Chen, Mei; Ding, Jingyi; Wang, Fang; Jin, Jingbo; Fan, Sitong; Chen, Jiajia (Frontiers in Medicine, 2022)
An 82-year-old male patient was hospitalized in the Respiratory Department for “repeated cough and shortness of breath for 10 years, recurrence worsened for 1 month.” Later, he was transferred for further diagnosis and treatment, to the Infectious Disease Department for further hospitalization. Previously, the patient had repeatedly undergone tuberculosis-related examinations including bronchoscopy examinations. However, no evidence of Mycobacterium tuberculosis (MTB) infection was found. Early anti-infection treatments failed. Due to repeated symptoms, we performed bronchoscopy again and sent alveolar lavage fluid for the metagenomic next-generation sequencing (mNGS) test. Subsequently, MTB and Candida albicans were detected by mNGS. After antituberculosis and antifungal treatments, the symptoms were significantly relieved, and the chest CT showed resolution of the lung lesions. Therefore, we successfully diagnosed and treated a case of recurrent pneumonia with tuberculosis and Candida co-infection diagnosed by mNGS.